Ethnobotany of natural dyes of futus woven fabrics used by Dawan Tribe in North Central Timor Regency - Bria, Emilia Juliyanti; Bani, Polikarpia Wilhelmina; Hanas, Dicky Frengky; Bano, Elinora Naikteas; Tefa, Yofrida (Jurnal Biologi Udayana; Vol 27 No 1 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i01.p10, 2023)
Futus is a term used by the Dawan people to refer to woven fabrics produced by the ikat technique which is applied in the yarn dyeing process. This woven cloth is one of the local pearls of wisdom passed down from generation to generation in the Dawan Tribe, North Central Timor District. The dyeing process is an important stage in the processing of woven fabrics that use plants as dyes. This study aims to reveal the types of natural coloring plants for woven fabrics, the plant organs used, and how they are processed. The semi-structured interview method was used in focus group discussions with 38 respondents who are weavers. This study revealed that there are 17 species from 12 plant families that are used as dyes for woven fabrics of the Dawan tribe in the North Central Timor District. Turmeric ( Curcuma longa L.) is the most widely used plant. The part of the plant most used as a dye is the leaves, followed by rhizomes, roots, bark, fruit, and seeds. The processing of plants into dyes for woven fabrics consists of two ways, namely boiling and without boiling, each of which produces a different color with a different fixative mixture.